Manufacturing of fiber-reinforced concrete bridge arches - M. R. Nakhaev (Вестник Дагестанского государственного технического университета: Технические науки)
Objective. A new method of manufacturing arches for a fiber-reinforced concrete bridge in the form of an analogue of permanent formwork is considered. Within the framework of this work, research results have been obtained that confirm the effectiveness of the system for the construction of bridge arches of various configurations.Method. The proposed developments will improve the strength characteristics of the bridge arch for small and medium bridges by optimizing the shape and size of the cross section in accordance with the change in the bending moment along the length of the arch. At the same time, reduce its metal consumption by several times.Result. The results obtained confirmed the effectiveness of electrostatic spraying of dry concrete mixture with simultaneous moisture up to moisture, which contributes to the work of capillary forces for compaction of concrete layers and the manufacture of a profiled strong shell (analogue of non-removable reinforced formwork) from reinforced fiber-reinforced concrete.Conclusion. By varying the shape and dimensions of the cross- section, the thickness of the shell and the degree of its reinforcement, as well as filling this shell with high-strength fiber-reinforced concrete, it is possible to design and manufacture bridge arches for various loads.